Effect of Collagen Crosslinkers on Dentin Bond Strength of Adhesive Systems: A Systematic Review and Meta-Analysis - Louis Hardan; Umer Daood; Rim Bourgi; Carlos Enrique Cuevas-Suárez; Walter Devoto; Maciej Zarow; Natalia Jakubowicz; Juan Eliezer Zamarripa-Calderón; Mateusz Radwanski; Giovana Orsini; Monika Lukomska-Szymanska (Cells, 2022)
This study aimed to identify the role of crosslinking agents in the resin–dentin bond strength (BS) when used as modifiers in adhesives or pretreatments to the dentin surface through a systematic review and meta-analysis. This paper was conducted according to the directions of the PRISMA 2020 statement. The research question of this review was: “Would the use of crosslinkers agents improve the BS of resin-based materials to dentin?” The literature search was conducted in the following databases: Embase, PubMed, Scielo, Scopus, and Web of Science. Manuscripts that reported the effect on the BS after the use of crosslinking agents were included. The meta-analyses were performed using Review Manager v5.4.1. The comparisons were performed by comparing the standardized mean difference between the BS values obtained using the crosslinker agent or the control group. The subgroup comparisons were performed based on the adhesive strategy used (total-etch or self-etch). The immediate and long-term data were analyzed separately. A total of 50 articles were included in the qualitative analysis, while 45 articles were considered for the quantitative analysis. The meta-analysis suggested that pretreatment with epigallocatechin-3-gallate (EGCG), carbodiimide, ethylenediaminetetraacetic acid (EDTA), glutaraldehyde, and riboflavin crosslinking agents improved the long-term BS of resin composites to dentin (p ≤ 0.02). On the other hand, the use of proanthocyanidins as a pretreatment improved both the immediate and long-term BS values (p ≤ 0.02). When incorporated within the adhesive formulation, only glutaraldehyde, riboflavin, and EGCG improved the long-term BS to dentin. It could be concluded that the application of different crosslinking agents such as carbodiimide, EDTA, glutaraldehyde, riboflavin, and EGCG improved the long-term BS of adhesive systems to dentin. This effect was observed when these crosslinkers were used as a separate step and when incorporated within the formulation of the adhesive system.